2017
DOI: 10.1186/s12874-017-0460-z
|View full text |Cite
|
Sign up to set email alerts
|

Abstract analysis method facilitates filtering low-methodological quality and high-bias risk systematic reviews on psoriasis interventions

Abstract: BackgroundArticle summaries’ information and structure may influence researchers/clinicians’ decisions to conduct deeper full-text analyses. Specifically, abstracts of systematic reviews (SRs) and meta-analyses (MA) should provide structured summaries for quick assessment. This study explored a method for determining the methodological quality and bias risk of full-text reviews using abstract information alone.MethodsSystematic literature searches for SRs and/or MA about psoriasis were undertaken on MEDLINE, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Methodologists have performed interesting work to aid in establishing the confidence of the results and conclusions of systematic reviews; however, more work is needed regarding systematic review abstracts. A study performed by Gómez-García et al [35] found that, on average, only 57% of the PRISMA-A items were included in the abstracts of systematic reviews and meta-analyses covering psoriasis treatments. They reported that studies with low-risk bias and high methodological quality had significantly more PRISMA-A items reported compared with studies with high-risk bias and low methodological quality.…”
Section: Recommendationsmentioning
confidence: 99%
“…Methodologists have performed interesting work to aid in establishing the confidence of the results and conclusions of systematic reviews; however, more work is needed regarding systematic review abstracts. A study performed by Gómez-García et al [35] found that, on average, only 57% of the PRISMA-A items were included in the abstracts of systematic reviews and meta-analyses covering psoriasis treatments. They reported that studies with low-risk bias and high methodological quality had significantly more PRISMA-A items reported compared with studies with high-risk bias and low methodological quality.…”
Section: Recommendationsmentioning
confidence: 99%
“…Gómez-García. 2017 [36] To assess abstracts reporting quality and to determine if the PRISMA-A indirectly captures the methodological quality and the risk of bias in the full texts.…”
Section: Number Of Abstracts (Year Range) Main Findings Of Abstracts ...mentioning
confidence: 99%
“…endorsement, [26 , 36 , 47] positive outcomes statistical significance, [5 , 11] higher methodological quality, [26 , 27 , 36] less spin in the abstracts, [26] European countries, [41] and academic funding source. [36] On the other hand, some studies have found different results for the same variables, showing no association of abstracts' reporting quality with: publication year, [26 , 35 , 39] abstract word count, [32 , 36 , 39 , 41] journal impact factor, [5 , 36 , 41] number of centers, [26 , 35 , 36 , 38 , 39] number of authors, [3 , 32 , 35 , 38 , 39 , 41 , 46 , 49] abstract format, [26 , 27 , 29 , 35 , 36 , 39 , 41] reporting guidelines endorsement, [3 , 5 , 11 , 29 , 41] outcomes statistical significance, [35 , 38-40 , 43 , 46 , 47] methodological quality, [27] continent of first author [5 , 26 , 35 , 38-40 , 46] and funding source. [5 , 11 , 39 , 47] The most common items not adequately reported (less than 50% of abstracts reporting) from the CONSORT-A were: randomization, blinding, funding, numbers analyzed, harms, authors, trial design, participants, primary outcomes results, registration, number randomized, clearly defined primary outcomes, recruitment status, conclusions, interventions and objectives.…”
Section: Sriganesh 2017 [47]mentioning
confidence: 99%
“…For some domains, this information may not be enough to achieve high performance in text mining tasks (Gonçalves et al, 2018). Also, the bias risk caused by abstract's quality and completeness exists (Gómez-García et al, 2017). The full text analysis has shown that substantial differences in profile and orientation can occur within the categories, such as methodological or empirical research (Glenisson et al, 2005).…”
Section: Journal Of Data and Information Sciencementioning
confidence: 99%